Analysis of Antenatal Care Implementation in Reducing Maternal and Infant Mortality Rates at Community Health Center in Medan City - Dany, Cut Nasywa Kesuma; Hasibuan, Rapotan (Karya Kesehatan Siwalima, 2025)
One of the primary targets of the Sustainable Development Goals (SDGs) 2030 and a key indicator of national development success is the reduction of maternal mortality (MMR). Because maternal health significantly influences the health of the next generation, antenatal care services are utilized to reduce MMR. The purpose of this study was to explore the inputs, processes, and outputs of antenatal care services provided by Community Health Centers (Puskesmas) in Medan City. A qualitative descriptive phenomenological method was employed, generating descriptive data. The study involved two main informants, one key informant, and five triangulation informants. Data were collected through in-depth interviews. The findings revealed that a high level of community preference for specialist services contributed to many cases of maternal and infant mortality as well as a decline in antenatal care visits at Puskesmas. In addition, the study identified the limited effectiveness of ultrasound examinations, which were only conducted once a week. Complaints from patients also emerged regarding the health workers’ approach, particularly their responsiveness, focus, and attentiveness, which led many patients to prefer specialists over Puskesmas services. Based on these findings, it is recommended that Puskesmas in Medan City address the issue of overlapping workloads, improve the standardization of supporting facilities, and increase the frequency of ultrasound examinations to twice per week.